Pre-season and in-season internal training load quantification of one-week schedules in under-17 European soccer team - Oliveira, R.; Brito, J. M.; Martins, A. (Journal of Human Sport & Exercise, 2019)
The aim of this study was to compare internal training load (ITL) of starters versus non-starters from the same under-17 soccer team. Rated of perceived exertion was collected and then multiplied by training or match duration (s-RPE) from twenty-three soccer players. The study analysed a total of 2 matches and 8 training sessions during the in-season with ANOVA with repeated measures. The main results showed higher values in pre-season for training duration (103.3 vs 90.0 min, p=0.000) in MD-5 and (103.7 vs 96.7 min, p>0.05) in MD-3 than in-season, but lower values for training duration (103.2 vs 112.0 min, p=0.013) in MD-4 and (84.0 vs 97.2 min, p=0.000) in MD-2 than in-season. s-RPE was higher in pre-season than in-season (725.5 vs 481.3 a.u., p=0.000) in MD-5 and (755.8 vs 655.2 a.u., p=0.031) in MD-3 but lower (705.2 vs 821.3 a.u., p=0.002) in MD-4 and (476.0 vs 559.0 a.u., p=0.020) in MD-2 than in-season. This study present relevant additional ITL data for pre-season and in-season that could be used to adjust periodization in under-17 soccer players.